Characterizing reduced height wheat mutants for traits affecting abiotic stress and photosynthesis during seedling growth. Issue 1 (1st February 2021) - Mohan, Amita; Grant, Nathan P.; Schillinger, William F.; Gill, Kulvinder S.
Abstract: Most high‐yielding, semidwarf wheat ( Triticum aestivum L.) grown around the world contains either Rht1 or Rht2 genes. The success of these high‐yielding cultivars is greatest in the most productive farming environments but provide marginal benefits in less favorable growing conditions such as shallow soils and low‐precipitation dryland farming. Further, growing evidence suggests semidwarf genes not only affect early seedling growth but limit grain yield, especially under abiotic stress conditions. There are 23 other reduced‐height mutants reported in wheat, most of which have not been functionally characterized. We evaluated these mutants along with their parents for several traits affecting seedling emergence, early seedling growth, and photosynthetic efficiency. Two‐ to seven‐fold differences in coleoptile length, first leaf length, root length, and root angle were observed among the genotypes. Most of the mutations had a positive effect on root length, while the root angle narrowed. Coleoptile and first leaf lengths were strongly correlated with emergence. A specialized deep planting experiment identified Rht5, Rht6, Rht8, and Rht13 with significantly improved seedling emergence compared to the parent. Among the mutants, Rht4, Rht19, and Rht12 ranked highest for photosynthetic traits while Rht9, Rht16, and Rht15 performed best for early seedling growth parameters. Considering all traits collectively, Rht15 showed the most promise for utilization in marginal environments followed by Rht19 and Rht16 . These wheat mutants may be useful for deciphering the underlying molecular mechanisms of understudied traits and breeding programs in arid and semiarid regions where deep planting is practiced.